Learning trauma in elementary social studies classrooms (IPS): a phenomenological inquiry - Aramudin; Omah Mukarromah; R. Toni Taufik; R. Hariyani Susanti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Emotional experiences significantly shape students’ engagement and academic identity, yet subject-specific learning trauma in elementary Social Studies remains underexplored. This study explored the lived experiences of elementary students who encountered learning trauma—defined as a pedagogical phenomenon of repeated emotional distress, not a clinical diagnosis—during Social Studies instruction. A qualitative phenomenological approach was employed. Data were collected through semi-structured interviews with eight purposively selected students (grades 4–6) from two elementary schools in Pekanbaru, Indonesia, who reported experiencing repeated negative emotions during Social Studies lessons. Data were analyzed using Colaizzi’s phenomenological method. Four essential themes emerged: fear of public humiliation, anxiety toward evaluation and memorization, emotional withdrawal, and defensive avoidance behaviors. These experiences were shaped by evaluative classroom practices and teacher-centered instruction, not extreme events. The findings suggest that learning trauma can arise from routine emotional injuries in the classroom. Practical implications include minimizing public correction (e.g., providing individual feedback privately), shifting from memorization-based to inquiry-driven assessment, and embedding trauma-informed emotional safety strategies—such as predictable routines and supportive teacher–student relationships—into daily Social Studies teaching.